Production and processing method of fine pen-type luminous LOGO product

In the production process of laptop-type luminescent LOGO products, nanoimprinting technology is used to manufacture micro-texture structures, and combined with radio frequency plasma treatment and high-precision automatic dispenser for material bonding, the problem of poor material bonding in the existing technology is solved and the high precision and high quality of the product is achieved.

CN119795609AInactive Publication Date: 2025-04-11ZHEJIANG RANHONG ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411863816.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When producing laptop-type luminescent LOGO products, it is difficult to achieve fine structure processing, material fit firmness and processing accuracy control, resulting in uneven product quality and cannot meet high-end market demand.

Method used

Transparent PET, transparent PC and diffusion film are used as basic materials, and micro-textured structures are created through nanoimprinting technology, combined with radio frequency plasma treatment and high-precision automatic dispensing machine for material bonding, and precision processing is carried out through UV light curing and five-axis linkage machining center.

Benefits of technology

It achieves a close fit between material layers, reduces bubbles and layering phenomena, improves the structural stability and optical performance of the product, and meets the requirements of the high-end market for appearance refinement and optical effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795609A_ABST
    Figure CN119795609A_ABST
Patent Text Reader

Abstract

The invention discloses a production and processing method of a fine pen-type luminous LOGO product. The production and processing method comprises the following steps: S1, material preparation and pretreatment; s2, carrying out plasma treatment; s3, dispensing and laminating the PET and the PC; s4, UV light curing is carried out; s5, attaching the PC to the diffusion film; s6, processing design; s7, processing operation; and S8, quality detection. In the step S1, a specific micro texture structure is manufactured on the surface of the material through the nanoimprint technology. The roughness of the surface of the material can be increased through micro texture treatment, so that surface gaps can be better filled with glue during coating, and bubbles formed by tiny air gaps between the glue and the material due to the fact that the surface is too smooth are avoided; and on the other hand, during fitting, the texture structure can play a role similar to mortise and tenon, so that the adjacent material layers are in closer contact, the mechanical occlusion effect is enhanced, and layering is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic product manufacturing, and in particular to a production and processing method of a fine notebook type luminous LOGO product. Background Art

[0002] With the continuous development of the notebook computer market, consumers have increasing requirements for the personalization, refinement and quality of product appearance. As a key element to highlight brand characteristics and product uniqueness, the quality of the production and processing methods of luminous LOGOs for laptops directly affects the overall aesthetics and performance of the product. However, the current traditional production and processing methods face many challenges in dealing with fine structures, ensuring the firmness of material fitting, and controlling processing accuracy. In the current bonding process on the market, bubbles and stratification problems are prone to occur during the bonding of the LOGO and the laptop, which will lead to uneven product quality and fail to meet the high-end and refined market demand. Accordingly, this application proposes a production and processing method for fine luminous LOGO products for laptops. Summary of the invention

[0003] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a production and processing method for a fine notebook type luminous LOGO product.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A production and processing method of a fine notebook type luminous LOGO product, comprising the following steps:

[0006] S1. Material preparation and pretreatment: transparent PET, transparent PC and diffusion film are selected as basic materials, and UV glue is used for bonding between materials. After the material pretreatment, micro-texture treatment is performed on the surfaces to be bonded of the basic materials such as transparent PET, transparent PC and diffusion film used for the luminous LOGO;

[0007] S2, plasma treatment, the side of the PET material with the nano-convex texture and the electroplating layer is plasma treated with a radio frequency plasma treatment device to enhance its adhesion with the UV glue;

[0008] S3, glue dispensing and laminating of PET and PC, using an automatic glue dispensing machine equipped with a high-precision metering system and a micro-sprinkler to dispense glue on the surface of the PET electroplating layer after plasma treatment, and then laminating the PC small piece material with the ring-shaped nano-groove texture with the glued PET material;

[0009] S4, UV light curing. After bonding, the bonded parts are sent to the UV light curing equipment to cure the UV glue under ultraviolet light with a wavelength of 365nm-395nm. The curing time is accurately set between 15-20 seconds according to the glue characteristics and material thickness to ensure that the glue is completely cured;

[0010] S5, PC and diffusion film are bonded, and the other side of the PC sheet with the ring-shaped nano-groove texture is glued again using an automatic glue dispensing machine according to the above glue dispensing requirements, and the diffusion film with the diamond-shaped nano-groove texture is bonded to the glued PC surface, and the air between the bonding surfaces is removed by a vacuum adsorption platform, and the glue is cured again by a UV light curing device;

[0011] S6. Processing design: According to the shape, size and processing requirements of the luminous LOGO product, a five-axis linkage machining center is used to process and manufacture the vacuum adsorption fixture. The aperture, spacing and direction parameters of the vacuum adsorption channel inside the fixture are optimized through computer simulation fluid mechanics analysis to ensure uniform and stable adsorption force when the material is adsorbed;

[0012] S7, machining operation, select a milling cutter with a diameter of 0.4mm for machining, determine the machining parameters of machining speed ranging from 1000mm / min to 5000mm / min, feed range ranging from 0.02mm / z to 0.1mm / z, and cutting depth ranging from 0.05mm to 0.2mm according to the product material structure requirements and tool performance, and solidify them into the control system of the machining equipment, and perform machining operations according to the solidified parameters;

[0013] S8. Quality inspection: Use a high-precision three-dimensional coordinate measuring instrument and an ultra-depth-of-field microscope to inspect the appearance and size of the finished product to ensure that there are no scratches, bubbles, delamination and other defects on the product surface. Then, inspect the optical properties of the luminous LOGO, and finally conduct a reliability test on the finished product.

[0014] Preferably, the nanoimprinting technology produces a specific microscopic texture structure on the surface of the material, such as regularly arranged nano grooves or protrusions.

[0015] Preferably, the metering system accuracy of the automatic glue dispensing machine reaches ±0.005ml, and the micro-sprinkler can accurately control the size and spacing of glue droplets.

[0016] Preferably, the motion accuracy of each axis of the five-axis linkage machining center is controlled within ±0.001 mm.

[0017] Preferably, the processing speed ranges from 1000 mm / min to 5000 mm / min, the feed rate ranges from 0.02 mm / z to 0.1 mm / z, and the cutting depth ranges from 0.05 mm to 0.2 mm.

[0018] Preferably, the plasma power adjustment range of the RF plasma processing equipment is 100W-500W, the processing time range is 10 seconds-60 seconds, and the gas flow adjustment range is 20sccm-80sccm.

[0019] Preferably, the size, depth, spacing and other parameters of the texture are precisely designed according to the optical properties of different materials and the functional requirements of the bonding parts to ensure that while solving the bonding problem, it will not have a negative impact on light propagation and product appearance.

[0020] The present invention has the following beneficial effects:

[0021] 1. During the material preparation process, the transparent PC material is cut by high-precision laser cutting technology, and the dimensional tolerance of the small piece of material is strictly controlled within ±0.05mm. At the same time, the cutting edge is guaranteed to be smooth and burr-free, laying the foundation for subsequent precise fitting and fine processing, so that the final luminous LOGO product can present precise shape and size, perfectly display the design details, and meet the strict requirements of high-end laptops for refined appearance.

[0022] 2. During the pretreatment process, the surface of the basic materials such as transparent PET, transparent PC and diffusion film used for the luminous LOGO is micro-textured, and the nano-imprinting technology is used to create a specific micro-texture structure on the surface of the material, such as regularly arranged nano grooves or protrusions. These micro-textures can increase the roughness of the material surface, so that the glue can better fill the surface gaps when applying, and avoid the formation of bubbles due to the tiny air gap between the glue and the material caused by the surface being too smooth; on the other hand, when fitting, this texture structure can play a role similar to "mortise and tenon", making the contact between adjacent material layers closer, enhancing the mechanical bite effect, and reducing stratification.

[0023] 3. During the material bonding process, the PET electroplating layer is plasma treated to increase its surface stress value to more than 50mN / m, which improves the wettability and activity of the material surface. The high-precision automatic dispensing machine is used for dispensing (the error of the glue droplet diameter is controlled within ±0.02mm, and the error of the glue point spacing is controlled within ±0.03mm) and precise bonding positioning (the relative position accuracy is controlled within ±0.05mm). The UV light curing parameters are then precisely controlled to achieve complete curing of the glue, so that each material layer can achieve a tight and firm bonding effect. This optimized bonding process not only ensures the structural stability of the luminous LOGO during long-term use, but also effectively avoids problems such as uneven light scattering and local luminescence abnormalities caused by poor bonding, ensuring the consistency and durability of the luminous effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a flow chart of the production and processing method. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0026] A production and processing method of a fine notebook type luminous LOGO product, comprising the following steps:

[0027] S1. Material preparation and pretreatment: select transparent PET, transparent PC and diffusion film as basic materials, and use UV glue for bonding between materials;

[0028] S2, plasma treatment, the side of the PET material with the nano-convex texture and the electroplating layer is plasma treated by radio frequency plasma treatment equipment, the plasma power range is adjusted to 200W, the treatment time range is 20 seconds, and the gas flow adjustment range is 30sccm, so that the surface stress value of the PET electroplating layer is further increased to more than 65mN / m, and its adhesion with the UV glue is enhanced;

[0029] S3, PET and PC are glued together. An automatic glue dispenser equipped with a high-precision metering system (accuracy of ±0.005ml) and a micro-sprinkler (capable of accurately controlling the size of glue drops, with the error of glue drop diameter controlled within ±0.015mm and the error of glue point spacing controlled within ±0.02mm) is used to dispense glue on the surface of the PET electroplating layer after plasma treatment. Then, a small piece of PC material with an annular nano-groove texture is bonded to the glued PET material. The relative position accuracy of the two is controlled within ±0.03mm. Since the micro-textures on the surfaces of PET and PC materials are compatible with each other, during bonding, the nano-protrusions of PET can be embedded in the annular grooves of PC, playing a role similar to "mortise and tenon joints", making the bonding tighter and effectively reducing the air residue between the bonding surfaces.

[0030] S4, UV light curing. After bonding, the bonded parts are sent to the UV light curing equipment to cure the UV glue under ultraviolet light with a wavelength of 365nm-395nm. The curing time is accurately set between 15-20 seconds according to the glue characteristics and material thickness to ensure that the glue is completely cured;

[0031] S5. PC and diffusion film are bonded. On the other side of the PC sheet with the ring-shaped nano-groove texture, an automatic glue dispenser is used to dispense glue again according to the above glue dispensing requirements. The diffusion film with the diamond-shaped nano-groove texture is bonded to the PC surface after glue dispensing. After the air between the bonding surfaces is removed with the help of a vacuum adsorption platform, the glue is cured again with a UV light curing device. The texture structure of the diffusion film and the surface of the PC material cooperate with each other. On the one hand, the glue can better fill the texture gaps and avoid the generation of bubbles; on the other hand, after bonding, the mechanical bite effect is further enhanced, making the connection between the material layers more stable, and the diffusion of light is more uniform, which improves the overall optical performance of the luminous LOGO;

[0032] S6. Processing design: According to the shape, size and processing requirements of the luminous LOGO product, a five-axis linkage machining center (the motion accuracy of each axis is controlled within ±0.001mm) is used to process and manufacture the vacuum adsorption fixture, so that the flatness of the fixture meets ±0.01mm and the surface roughness Ra reaches below 0.8μm. The aperture, spacing and direction parameters of the vacuum adsorption channel inside the fixture are optimized through computer simulation fluid mechanics analysis to ensure uniform and stable adsorption force when the material is adsorbed;

[0033] S7, machining operation, select a milling cutter with a diameter of 0.4mm for machining, determine the machining parameters of machining speed range of 1000mm / min-5000mm / min, feed range of 0.02mm / z-0.1mm / z, and cutting depth range of 0.05mm-0.2mm according to product material requirements and tool performance, and solidify them into the control system of the machining equipment, perform machining operations according to the solidified parameters, and control the machining size tolerance within ±0.01mm and the shape tolerance within ±0.005mm;

[0034] S8. Quality inspection: Use a high-precision three-dimensional coordinate measuring instrument and an ultra-depth-of-field microscope to inspect the appearance and size of the finished product to ensure that there are no scratches, bubbles, delamination and other defects on the product surface. Then, inspect the optical properties of the luminous LOGO, and finally conduct a reliability test on the finished product.

[0035] Embodiment 1:

[0036] Step 1: Material preparation:

[0037] First, select a high-quality transparent PET coil with a thickness of 0.3mm to ensure that the material itself has good transparency and flexibility. Perform routine cleaning on it, use an ultrasonic cleaner to clean it in an isopropyl alcohol solution for 10 minutes to remove dust, oil and other impurities on the surface, and then dry it naturally for use.

[0038] Then the template required for nanoimprinting technology was designed and made. According to the characteristics of PET materials and the requirements of the luminous LOGO for fitting and optical performance, a template composed of nano-conical protrusions arranged in regular hexagons was designed. The height of the conical protrusions is set to 120 nanometers, the bottom diameter is 180 nanometers, and the center spacing of adjacent conical protrusions is 300 nanometers. This texture structure helps to increase the surface roughness of the material and the mechanical bite effect when it is subsequently fitted with other materials. The template is manufactured using high-precision electron beam lithography and subsequent micro-nano processing technology to ensure that the dimensional accuracy error of the texture structure on the template is controlled within ±5 nanometers to ensure the accuracy and consistency of the imprinted microtexture. During the nanoimprinting operation, a layer of UV-curable imprinting glue with a thickness of about 80 nanometers is evenly coated on the surface of the cleaned PET material. This is achieved through a spin coating process. The spin coating speed is set to 1200 rpm for 50 seconds. Align the prepared template with nanocone convex texture to the PET material and gently cover it, then apply a pressure of 6MPa through the embossing equipment, while maintaining the ambient temperature at 25°C, and set the embossing time to 8 minutes, so that the embossing glue can fully fill the texture structure of the template. Finally, use UV light with a wavelength of 365nm for 3 minutes for curing. After curing, slowly demold at a demolding angle of about 8 degrees to obtain a transparent PET material with regular nanocone convex texture.

[0039] Select a transparent PC sheet that meets the requirements, and use high-precision cutting equipment to cut it into small pieces of material of appropriate size. The size of the small piece is determined according to the design requirements of the luminous LOGO, for example, it is cut into a square piece with a side length of 40mm, and the cutting size tolerance is strictly controlled within ±0.03mm. At the same time, the cutting edge is finely polished to make it smooth and burr-free to ensure the accuracy requirements of subsequent processing and bonding. The template design of nanoimprint technology is also carried out. Considering the bonding of PC material and diffusion film and the light propagation characteristics, a wavy nano-groove template is designed. The groove depth is set to 150 nanometers, the width is 220 nanometers, and the peak spacing of adjacent wavy grooves is 450 nanometers. It is expected that this texture will make the glue fill better and enhance the scattering effect of light when bonding the diffusion film. The template is manufactured by professional micro-nano processing methods to ensure the quality of the template and make its texture size accuracy error within the range of ±8 nanometers. Nanoimprinting operation was performed on the surface of the PC small sheet material. First, a 70-nanometer-thick layer of UV-curable imprinting glue was coated (spin coating speed of 1000 rpm, time of 60 seconds), and then the wavy groove template was aligned with the material for imprinting. A pressure of 7 MPa was applied and imprinting was performed for 7 minutes at a constant temperature of 28°C. After that, it was cured by irradiating with UV light with a wavelength of 380 nm for 2.5 minutes. After careful demolding, a transparent PC material with a wavy nano-groove texture was obtained.

[0040] The diffusion film is cut with high-precision cutting equipment. According to the size planning of the luminous LOGO product, the diffusion film is cut into specifications with a width of 35mm. The cutting width accuracy is within ±0.05mm to ensure that the size meets the requirements of subsequent bonding and overall product design. A nanoimprint template is designed for the diffusion film, using a composite texture structure. The bottom layer of the template is composed of small nano grooves arranged in a diamond shape, with a groove depth of 60 nanometers, a width of 100 nanometers, and a spacing of 180 nanometers; the upper layer is sparsely distributed larger nano cylindrical protrusions, arranged in a rectangular shape, with a protrusion height of 100 nanometers, a bottom diameter of 150 nanometers, and a spacing of 300 nanometers between adjacent cylindrical protrusions. This composite texture is designed to take into account both the mechanical bite when bonding with the PC material and the uniform diffusion effect of light. After the composite texture template is carefully made (the texture size accuracy error is controlled at about ±10 nanometers), a 50-nanometer-thick embossing glue is coated on the surface of the cut diffusion membrane (spin coating speed is 800 rpm, time is 40 seconds), the composite texture template is aligned with the diffusion membrane for embossing, a pressure of 5 MPa is applied, and embossing is performed at room temperature for 6 minutes. Then, it is irradiated with UV light with a wavelength of 370 nm for 2 minutes to cure and demold, thereby obtaining a diffusion membrane material with a specific composite microtexture.

[0041] Step 2: Fitting:

[0042] On one side of the electroplating layer of the PET material with nano-conical protrusion texture, plasma treatment was performed using radio frequency plasma treatment equipment. The plasma power was adjusted to 250W, the treatment time was 25 seconds, and the gas flow rate was 40sccm, so that the stress value of the surface of the PET electroplating layer was increased to 68mN / m, further enhancing its adhesion to the UV glue.

[0043] An automatic dispensing machine equipped with a high-precision metering system (accuracy of ±0.003ml) and a micro-sprinkler (glue drop diameter error is controlled within ±0.012mm, glue point spacing error is controlled within ±0.018mm) is used to dispense glue on the surface of the PET electroplating layer after plasma treatment, and then the PC small piece with wavy nano-grooved texture is bonded to the PET material after dispensing, and the relative position accuracy of the two is controlled within ±0.025mm. Since the nano-conical protrusions of PET can adapt to the wavy nano-grooves of PC, during the bonding process, they are embedded in each other like a "mortise and tenon" structure, which effectively reduces the air residue between the bonding surfaces and makes the bonding tighter.

[0044] After bonding, the bonded parts are sent to the UV light curing equipment to cure the UV glue under ultraviolet light with a wavelength of 365nm-385nm. The curing time is precisely set to 18 seconds according to the glue properties and material thickness to ensure that the glue is fully cured and the PET and PC materials are firmly connected.

[0045] Step 3: Machining:

[0046] According to the shape, size and processing requirements of the luminous LOGO product, a five-axis linkage machining center (the motion accuracy of each axis is controlled within ±0.001mm) is used to manufacture the vacuum adsorption fixture, so that the flatness of the fixture meets ±0.008mm and the surface roughness Ra reaches below 0.6μm. The aperture, spacing and direction parameters of the vacuum adsorption channel inside the fixture are optimized through computer simulation fluid mechanics analysis to ensure uniform and stable adsorption force when the material is adsorbed.

[0047] Place the bonded materials on the vacuum adsorption fixture, start the vacuum adsorption system to adsorb the materials, and use the visual inspection system combined with manual assisted inspection to ensure that the materials are not warped, wrinkled, or not completely adsorbed and bonded.

[0048] In view of the structural feature of extremely small R angle in the product, a milling cutter with a diameter of 0.4mm is selected for processing, and a high-precision strain sensor and tool damage detection device are installed on the milling cutter handle to monitor the force condition and blade integrity of the tool during the cutting process in real time, and automatically stop processing when an abnormality is detected.

[0049] According to the product material characteristics, structural requirements and tool performance, the processing parameters of processing speed range of 1500mm / min-4000mm / min, feed range of 0.025mm / z-0.08mm / z and cutting depth range of 0.06mm-0.15mm are determined and solidified into the control system of the processing equipment. Machining operations are performed according to the solidified parameters to control the processing size tolerance within ±0.008mm and the shape tolerance within ±0.003mm.

[0050] Embodiment 2:

[0051] Step 1: Material preparation:

[0052] A transparent PET coil with a thickness of 0.3 mm was selected for conventional chrome plating, and the thickness of the chrome plating layer was controlled at 0.05 μm. Anti-aging agents and ultraviolet absorbers were added. Then, a chemical etching method was used to create micro-textures, as follows:

[0053] Sodium hydroxide solution is selected as an etching agent, and the concentration is adjusted to 8 mol / L. The PET material is immersed in the etching agent solution, the temperature is controlled at 30°C, and the etching time is set to 10 minutes. A periodic circular opening pattern (photoresist thickness is about 100 nanometers) is produced on the surface of the PET material by photoresist, the diameter of the opening circle is 200 nanometers, and the center spacing of adjacent circular openings is 400 nanometers. It is expected that a circular nano-groove structure will be formed in the opening area after etching. The PET material with the photoresist pattern is immersed in the etching agent solution for etching. After etching is completed, the photoresist is removed to obtain a PET material with a circular nano-groove texture on the surface. The groove depth is about 60 nanometers and the width is 100 nanometers. However, due to the isotropic characteristics of chemical etching, the groove shape and dimensional accuracy are relatively low, and the error range is about ±20 nanometers.

[0054] The transparent PC material is cut into small pieces in the conventional way, with the size tolerance controlled within ±0.05mm and the cutting edge is smooth. The chemical etching method is also used to produce the micro texture, as follows:

[0055] A mixed solvent containing halogenated hydrocarbon components is selected as an etchant, and the etchant is formulated to meet specific chemical ratio requirements. A square pattern is made on the surface of the PC material by photolithography technology as the area to be etched, with a side length of 300 nanometers and a spacing of 500 nanometers between adjacent squares.

[0056] The PC material is immersed in an etchant and etched at room temperature for 8 minutes to form a nanoscale recessed structure on the surface of the material in the square pattern area. The square recess formed after etching has a depth of about 50 nanometers and a width between 80 and 100 nanometers (the width fluctuates to a certain extent due to the unevenness of the etching process). The photoresist protective layer is then removed to obtain a PC material with a texture, but the uniformity and precision of the texture are not as good as the texture manufactured by the nanoimprint technology in Example 1.

[0057] After the diffusion film is cut to a width accuracy of ±0.1mm, chemical etching is used to create micro textures as follows:

[0058] A suitable strong acid solution (under strictly controlled conditions) is selected as the etchant, and the concentration is set to 5 mol / L. The pattern to be etched is made on the surface of the diffusion membrane through mask technology. The pattern is designed to be a hexagonal arrangement of small holes with a diameter of 150 nanometers and a center-to-center distance of 300 nanometers between adjacent small holes.

[0059] The diffusion membrane was immersed in an etchant solution, the temperature was maintained at 25°C, and the etching time was 12 minutes. After the etching was completed, the mask was removed to obtain a diffusion membrane with a hexagonal pore texture on the surface. The pore depth was about 70 nanometers, but the actual etched texture had a certain degree of non-uniformity in shape and depth. The size difference between the pores was relatively large, and the error could reach about ±30 nanometers.

[0060] Step 2: Fitting:

[0061] The electroplating layer of the PET material with chemical etching texture was treated with radio frequency plasma, with the power set to 200 W, the processing time to 20 seconds, and the gas flow rate to 30 sccm. The response value was increased to about 50 mN / m. However, due to the roughness and uniformity of the chemical etching texture on the PET surface, the response value improvement effect was not as ideal as the original embodiment.

[0062] An automatic glue dispensing machine was used to dispense glue, with the diameter error of the glue droplets controlled at ±0.025mm, and the distance between the glue dots controlled at ±0.035mm (the glue dispensing accuracy was reduced due to the influence of the surface texture). The PC small piece was bonded to the PET material with a relative position accuracy within ±0.06mm. During bonding, due to the uneven shape and size of the chemical etching texture, the compatibility between PET and PC was not as good as the texture structure in the original embodiment, resulting in more tiny gaps on the bonding surface, making it difficult for the air to be completely discharged.

[0063] The glue was cured with UV light of 365nm for 18 seconds, but due to the presence of many air gaps on the bonding surface, some bubbles still remained after the glue was cured, affecting the bonding quality.

[0064] After glue is applied to the other side of the PC, it is bonded to the diffusion film, also with the help of a vacuum adsorption platform. However, due to the uneven chemical etching texture of the diffusion film, some air still remains after bonding. After UV light curing, the firmness and tightness of the bonding are insufficient, and from the appearance, a slight unevenness can be observed at the bonding site.

[0065] Step 3: Machining:

[0066] According to the shape, size and processing requirements of the luminous LOGO product, a five-axis linkage machining center (the motion accuracy of each axis is controlled within ±0.001mm) is used to manufacture the vacuum adsorption fixture, so that the flatness of the fixture meets ±0.01mm and the surface roughness Ra reaches below 0.8μm. The aperture, spacing and direction parameters of the vacuum adsorption channel inside the fixture are optimized through computer simulation fluid mechanics analysis to ensure uniform and stable adsorption force when the material is adsorbed.

[0067] Place the bonded materials on the vacuum adsorption fixture, start the vacuum adsorption system to adsorb the materials, and use the visual inspection system combined with manual assisted inspection to ensure that the materials are not warped, wrinkled, or not completely adsorbed and bonded.

[0068] A 0.4mm milling cutter was used for processing, and the force threshold of the milling cutter was set to [corresponding reasonable value], the processing speed was 3000mm / min, the feed rate was 0.05mm / z, and the cutting depth was 0.1mm. Due to the uneven chemical etching texture on the surface of the material and the poor bonding effect, the tool force was unstable during the processing, and vibration and slight deflection were prone to occur, resulting in the final processed luminous LOGO product size tolerance exceeding ±0.02mm, shape tolerance exceeding ±0.01mm, luminous uniformity can only reach within ±12%, color deviation (△E) is greater than 3, and the overall product quality is significantly lower than the original embodiment, reflecting the important influence of the micro-texture processing method and parameter selection in the original embodiment on product quality.

[0069] Embodiment three:

[0070] Step 1: Material preparation:

[0071] A transparent PET coil with a thickness of 0.3mm was selected, and only conventional chrome plating was performed (chrome plating thickness 0.05μm). After adding anti-aging agents and ultraviolet absorbers, no micro-texture treatment was performed, and it was directly prepared for the subsequent bonding process. The transparent PC material was cut into small pieces, the dimensional tolerance was controlled within ±0.05mm and the cutting edge was smooth. The micro-texture treatment step was also omitted, and the material surface was kept smooth before entering the bonding process. The diffusion film was cut, and after the width accuracy of the diffusion film after cutting reached within ±0.1mm, it was not subjected to micro-texture treatment and was directly used in the subsequent processing flow.

[0072] Step 2: Fitting:

[0073] The electroplating layer of the untreated textured PET material was treated with radio frequency plasma, with the power set to 300 W, the treatment time to 30 seconds, and the gas flow rate to 40 sccm. The stress value was increased to about 52 mN / m. However, due to the smooth surface of the material, the increase in the stress value was limited, and the adhesion with the glue was relatively weak.

[0074] When using an automatic glue dispensing machine to dispense glue, the error in glue drop diameter is controlled at ±0.02mm, and the error in glue point spacing is controlled at ±0.03mm. When bonding the smooth PC piece to the PET material, the relative position accuracy is within ±0.04mm. However, due to the lack of assistance from micro-textures during bonding, more air is easily retained between the bonding surfaces, forming obvious bubbles, resulting in poor bonding tightness and unsatisfactory bonding effects.

[0075] After 20 seconds of UV curing with a wavelength of 365nm, the glue solidified, but bubbles still existed in the bonding surface, affecting the firmness of the bonding and the appearance quality of the product.

[0076] Step 3: Machining:

[0077] According to the shape, size and processing requirements of the luminous LOGO product, a five-axis linkage machining center (the motion accuracy of each axis is controlled within ±0.001mm) is used to manufacture the vacuum adsorption fixture, so that the flatness of the fixture meets ±0.01mm and the surface roughness Ra reaches below 0.8μm. The aperture, spacing and direction parameters of the vacuum adsorption channel inside the fixture are optimized through computer simulation fluid mechanics analysis to ensure uniform and stable adsorption force when the material is adsorbed.

[0078] Place the bonded materials on the vacuum adsorption fixture, start the vacuum adsorption system to adsorb the materials, and use the visual inspection system combined with manual assisted inspection to ensure that the materials are not warped, wrinkled, or not completely adsorbed and bonded.

[0079] A 0.4mm milling cutter was selected for processing, the milling cutter force threshold was set to [corresponding reasonable value], the processing speed was 3300mm / min, the feed rate was 0.052mm / z, and the cutting depth was 0.105mm. Due to the lack of micro-texture structure when the materials were bonded, the bonding quality was poor. During the processing, the materials were prone to delamination and displacement, which affected the stability of the tool cutting, and thus led to a decrease in processing accuracy. The final processed luminous LOGO product had a size tolerance exceeding ±0.02mm, a shape tolerance exceeding ±0.01mm, and a luminous uniformity of only ±15%. The color deviation (△E) was greater than 3.2. The overall quality of the product was far inferior to the original embodiment, highlighting the importance and necessity of micro-texture treatment of the material surface in the entire luminous LOGO product manufacturing process.

[0080] The bonding process parameters for each group of embodiments are shown in Table 1:

[0081] Table 1: Comparison of various parameters of the bonding process between the examples

[0082]

[0083]

[0084] The machining parameters of each group of embodiments are shown in Table 2:

[0085] Table 2: Comparison of various parameters in the machining stage between the embodiments

[0086]

[0087] In Example 1, after the micro-texture treatment manufactured by nanoimprinting technology, the amount of bubbles generated between the material layers during the bonding process was greatly reduced compared to the traditional process without texture treatment. In the actual operation comparison, it was found that the number of bubbles was reduced by about 85%, and the material layers after bonding were tightly fitted, and there was almost no poor bonding caused by residual air. The bonding strength was tested by tensile testing, and it was found that the tensile force required for delamination was 3 times higher than that of ordinary smooth surface bonding, which effectively enhanced the firmness of the bonding, ensured the structural stability of the luminous LOGO product during long-term use, and reduced quality problems caused by poor bonding.

[0088] Furthermore, for luminous LOGO products, the microscopic texture structure of the surface of different materials has a positive impact on the propagation of light. Under the action of the wavy nano-groove texture of the transparent PC material and the composite texture of the diffusion film, the light can be scattered and diffused more evenly when passing through these materials, avoiding the situation where the local light is too bright or too dark. After detection by professional optical testing equipment, the luminous uniformity is within ±4%, which is about 40% higher than that of untreated materials, significantly improving the visual effect of the luminous LOGO, making it present a softer, more uniform and high-quality light distribution when lit, enhancing the beauty and recognition of the product, and better meeting the user's requirements for the appearance of high-quality luminous LOGO.

[0089] In addition, during the machining process of the micro-textured material, the contact between the milling cutter and the material surface is improved due to the increased surface roughness, and the cutting process is smoother. In actual processing, the number of tool breakages is significantly reduced compared to when processing smooth surface materials, and the service life of the tool is also extended by about 35%. At the same time, because the materials fit tightly, there will be no processing accuracy problems caused by material stratification or displacement during the processing process. The final luminous LOGO product has a dimensional tolerance within ±0.008mm and a shape tolerance within ±0.003mm, which meets the requirements of fine notebook products for high-quality appearance and high precision, and improves the overall quality and market competitiveness of the product.

[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A production and processing method for a fine notebook type luminous LOGO product, characterized in that: The following steps are involved: S1. Material preparation and pretreatment: transparent PET, transparent PC and diffusion film are selected as basic materials, and UV glue is used for bonding between materials. After the material pretreatment, micro-texture treatment is performed on the surfaces to be bonded of the basic materials such as transparent PET, transparent PC and diffusion film used for the luminous LOGO; S2, plasma treatment, the side of the PET material with the nano-convex texture and the electroplating layer is plasma treated with a radio frequency plasma treatment device to enhance its adhesion with the UV glue; S3, glue dispensing and laminating of PET and PC, using an automatic glue dispensing machine equipped with a high-precision metering system and a micro-sprinkler to dispense glue on the surface of the PET electroplating layer after plasma treatment, and then laminating the PC small piece material with the ring-shaped nano-groove texture with the glued PET material; S4, UV light curing. After bonding, the bonded parts are sent to the UV light curing equipment to cure the UV glue under ultraviolet light with a wavelength of 365nm-395nm. The curing time is accurately set between 15-20 seconds according to the glue characteristics and material thickness to ensure that the glue is completely cured; S5, PC and diffusion film are bonded, and the other side of the PC sheet with the ring-shaped nano-groove texture is glued again using an automatic glue dispensing machine according to the above glue dispensing requirements, and the diffusion film with the diamond-shaped nano-groove texture is bonded to the glued PC surface, and the air between the bonding surfaces is removed by a vacuum adsorption platform, and the glue is cured again by a UV light curing device; S6. Processing design: According to the shape, size and processing requirements of the luminous LOGO product, a five-axis linkage machining center is used to process and manufacture the vacuum adsorption fixture. The aperture, spacing and direction parameters of the vacuum adsorption channel inside the fixture are optimized through computer simulation fluid mechanics analysis to ensure uniform and stable adsorption force when the material is adsorbed; S7, machining operation, select a milling cutter with a diameter of 0.4mm for machining, determine the machining parameters of machining speed ranging from 1000mm / min to 5000mm / min, feed range ranging from 0.02mm / z to 0.1mm / z, and cutting depth ranging from 0.05mm to 0.2mm according to product material requirements and tool performance, and solidify them into the control system of the machining equipment, and perform machining operations according to the solidified parameters; S8. Quality inspection: Use a high-precision three-dimensional coordinate measuring instrument and an ultra-depth-of-field microscope to inspect the appearance and size of the finished product to ensure that there are no scratches, bubbles, delamination and other defects on the product surface. Then, inspect the optical properties of the luminous LOGO, and finally conduct a reliability test on the finished product.

2. The production and processing method of a fine notebook type luminous LOGO product according to claim 1 is characterized in that: In the step S1, the nanoimprint technology is used to produce a specific microscopic texture structure on the surface of the material, such as regularly arranged nano grooves or protrusions.

3. The production and processing method of a fine notebook type luminous LOGO product according to claim 1 is characterized in that: In step S3, the metering system accuracy of the automatic dispensing machine reaches ±0.005ml, and the micro-sprinkler can accurately control the size and spacing of the glue droplets.

4. The production and processing method of a fine notebook type luminous LOGO product according to claim 1 is characterized in that: In step S6, the motion accuracy of each axis of the five-axis linkage machining center is controlled within ±0.001 mm.

5. The production and processing method of a fine notebook type luminous LOGO product according to claim 1 is characterized in that: In step S7, the processing speed range is 1000 mm / min-5000 mm / min, the feed rate range is 0.02 mm / z-0.1 mm / z, and the cutting depth range is 0.05 mm-0.2 mm.

6. The production and processing method of a fine notebook type luminous LOGO product according to claim 1 is characterized in that: In the step S2, the plasma power of the radio frequency plasma processing equipment is adjusted in the range of 100W-500W, the processing time is adjusted in the range of 10 seconds-60 seconds, and the gas flow rate is adjusted in the range of 20sccm-80sccm.

7. The production and processing method of a fine notebook type luminous LOGO product according to claim 1 is characterized in that: In step S1, the size, depth, spacing and other parameters of the texture are precisely designed according to the optical properties of different materials and the functional requirements of the bonding parts, ensuring that while solving the bonding problem, it will not have a negative impact on light propagation and product appearance.